Exploring the interplay between students’ scientific competence and teaching instructors’ TPACK: A comprehensive analysis - Sonsupap, Kanyarat; Cojorn, Kanyarat; Sitti, Somsong (International Journal of Innovative Research and Scientific Studies, 2025)
This exploratory research investigates the scientific competence levels among secondary school students in the North Eastern region of Thailand in the post-COVID-19 era and examines the relationship between teachers’ Technological Pedagogical Content Knowledge (TPACK) and students’ scientific competency. The study collects data from 76 science teachers and 1878 students representing 76 schools in the northeast of Thailand. The study employs a set of instruments, including 1) the 28 items of the TPACK questionnaire and 2) the scientific competency measurement tool. The findings reveal that the overall scientific competency score among students reflects a moderate level. Specifically, students demonstrated moderate competence in "explaining phenomena scientifically" and "evaluating and designing scientific inquiry," while their ability to "interpret evidence and data scientifically" was found to be at a low level. Furthermore, there is a significant but low-level correlation between the scientific competency of students and the TPACK of their teachers. The findings highlight the urgent need for a pedagogical shift in educational practices. There is a pressing need to design learning experiences that emphasize scientific inquiry and critical thinking rather than focusing solely on subject matter expertise. Strengthening teachers’ capacity to integrate technology with pedagogy alongside fostering inquiry-based learning approaches will be crucial in improving students’ scientific competencies and preparing them to handle challenging problems in the contemporary world.